Estrous cycle dependent neurovascular dysfunction induced by angiotensin II in the mouse neocortex - Capone, Carmen (2009)
Female mice are protected from the cerebrovascular dysfunction induced by angiotensin II (AngII), an effect attributed to estrogen. We examined whether such cerebrovascular protection from AngII is related to the estrous cycle. Cerebral blood flow (CBF) was monitored by laser-Doppler flowmetry in anesthetized (urethane-chloralose) C57BL/6 female mice equipped with a cranial window. The phase of the estrous cycle was determined by vaginal smear cytology and plasma estrogen measurement. AngII (0.25 μg/Kg/min; i.v.; 30-45 min) elevated arterial pressure (15-20 mmHg) equally across the estrous cycle. However, in proestrus and estrus, phases in which estrogen is relatively high, AngII did not impair the in increase in the CBF induced by neural activity or by endothelium-dependent vasodilators (p>0.05 from vehicle). In contrast, in diestrus (lower estrogen) AngII induced a marked cerebrovascular dysfunction comparable to that of males. For example, the CBF response to whisker stimulation and to the endothelium-dependent vasodilator acetylcholine were attenuated by 41±12% and 49±12%, respectively (p<0.05; n=6/group). The protection from the cerebrovascular effects of AngII in proestrus was abolished by the estrogen receptor inhibitor ICI182,780. AngII also increased production of free radicals in cerebral blood vessels in diestrus (+116±13%; p<0.05), but not in proestrus and estrus (p>0.05 from control). Topical treatment with ICI182,780 reestablished AngII-induced oxidative stress in proestrus (p>0.05 from diestrus). We conclude that the protection from the neurovascular dysfunction induced by acute administration of AngII in females depends on the estrous cycle and may underlie the increased propensity to cerebrovascular damage associated with low estrogen states.